Distinctive Gut Microbiota in Patients with Overweight and Obesity with Dyslipidemia and its Responses to Long-term Orlistat and Ezetimibe Intervention: A Randomized Controlled Open-label Trial - Jin, Jin; Cheng, Ruyue; Ren, Yan; Shen, Xi; Wang, Jiani; Xue, Yigui; Zhang, Huimin; Jia, Xiuhua; Li, Tingting; He, Fang; Tian, Haoming (Frontiers in Pharmacology, 2021)
This study investigated the gut microbiota and short chain fatty acids (SCFAs) characteristics of subjects with obesity from Xinjiang in northwestern China, a region with a multiethnic culture and characteristic lifestyle, and to explore the potential microbes that respond to a 12-week medication of orlistat and ezetimibe with a randomized controlled open-label trial manner. The gut microbiota profile of patients with overweight and obesity with dyslipidemia in Xinjiang was distinctive and characterized by enrichment of Lactobacillus and the reduction of the diversity and the depletion of Actinobacteria, Bacteroides, Bifidobacterium, and Bacteroides fragilis. Prevotella-type, Gemmiger-type, and Escherichia/Shigella-type were the gut microbial patterns of the Xinjiang population. However, the fecal SCFAs levels and enterotypes were similar between healthy individuals and patients. These results indicated that the contribution of the gut microbiota to obesity was highly dependent on geography and dietary habits. Waist circumference, total triglyceride (TG), and fasting blood glucose (FBG) were significantly decreased after orlistat therapy, whereas TG, total cholesterol (TC), and low density lipoprotein cholesterol (LDL-C) were significantly decreased by ezetimibe. Overall, the gut microbiota and their SCFAs metabolites were relatively stable after treatment with the two drugs, with alteration of some low-abundant bacteria, i.e., significantly increased Proteobacteria and decreased Alloprevotella after orlistat, and increased Fusobacteria and Fusobacterium after ezetimibe therapy. These results indicated that intestinal malabsorption of dietary fat and cholesterol caused by orlistat and ezetimibe had a limited effect on the overall gut microbial community and their metabolites. Nevertheless, significant correlations between several core microbes that responded to the medications and biochemical data were found; in particular, Actinomyces and Bacteroides were positively correlated with FBG after orlistat intervention, while Clostridium XVIII and Lachnospiracea incertae sedis were negatively correlated with TC and LDL-C after ezetimibe intervention, thus indicating their roles in improving glucolipid metabolism in obesity by acting as potential microbial targets.